Examining decision support systems (DSS) verification approaches of the government agencies in east Malaysia - Syed Nasirin Syed Zainol Abidin; Iza A. A. Bahar; Nooralisa Mohd. Tuah; Abdul Kadir; Carolyn Salimun; Soffri Yussof (Elsevier, 2024)
This study examines the verification approaches used by government agencies in East Malaysia to ensure the reliability of Decision Support Systems (DSS) in their decision-making processes. Focus group interviews were conducted, revealing various verification methods employed. The study aims to contribute to understanding DSS verification techniques and the unique challenges government agencies face. Challenges identified include a need for more technical expertise. It recommends investing in staff training and adopting standardized verification frameworks to enhance DSS reliability. These findings are valuable for East Malaysian government agencies and other similar contexts, enabling informed decision-making through reliable DSS.